Development of a Natural Antifungal Shampoo Containing Clove Bud Oil (Syzygium aromaticum): Formulation and in Vitro Evaluation - Afia Khaira; Tantri Nareswari; Refsya Azanti Putri; Achmad Gus Fahmi (Science and Technology Indonesia, 2026)
Dandruff affects approximately 50% of the global population during their lifetime. Clove bud oil (Syzygium aromaticum) (CBO), which is currently utilized mainly in the cigarette industry, has potential as an anti-dandruff agent because of its antifungal activity. This study aimed to optimize cocamide DEA and sodium lauryl sulfate (SLS) concentrations in CBO shampoo formulations and to evaluate the preliminary antifungal activity of the optimum formulation against Candida albicans as a model fungal organism, compared with a commercial ketoconazole shampoo (Ketomed®). CBO quality was characterized through organoleptic evaluation, specific gravity determination, ethanol solubility testing, Thin Layer Chromatography (TLC), and GC–MS analysis. GC–MS confirmed eugenol (76.88%) and β-caryophyllene (16.18%) as the major constituents of the oil. The shampoo formulations were prepared using the emulsification method followed by a two-stage surfactant optimization process. The first optimization identified 8% cocamide DEA as the optimum concentration, producing a viscosity of 3915 ± 59 cPs and foam height of 10.43 ± 0.20 cm. The second optimization demonstrated that 8% SLS provided the most favorable physicochemical characteristics and washing performance. The optimum formulation exhibited antifungal activity against C. albicans with an inhibition zone of 24.06 ± 3.01 mm, compared with 32.50 ± 1.44 mm for Ketomed®, which corresponded to approximately 74% relative antifungal efficacy. These findings suggest that CBO shampoo possesses promising potential as an antifungal anti-dandruff formulation while also providing an alternative value-added utilization of clove oil. This study was limited to in vitro evaluation against a single microorganism, C. albicans, and further in vivo and clinical studies remain necessary to confirm the efficacy and safety of the developed formulation.